Endogenous sex steroid hormones and glucose in a South‐Asian population without diabetes: the Metabolic Syndrome and Atherosclerosis in South‐Asians Living in America pilot study. Issue 9 (11th December 2014) - Needham, B. L.; Kim, C.; Mukherjee, B.; Bagchi, P.; Stanczyk, F. Z.; Kanaya, A. M.
Abstract Aims To examine the associations between endogenous sex steroid hormones (oestradiol, testosterone and sex hormone‐binding globulin) with diabetes risk in a South‐Asian population living in the USA. Methods We used data from the Metabolic Syndrome and Atherosclerosis in South‐Asians Living in America pilot study. The analytical sample included 60 women and 45 men of Asian Indian origin living in the San Francisco Bay Area, who were free from diabetes and cardiovascular disease and did not use exogenous sex steroids. Sex steroid hormone levels were assessed by validated conventional radioimmunoassays, and visceral and hepatic adiposity were assessed by computed tomography. We used multivariable regression to examine the association between endogenous sex steroid hormone levels (log‐transformed) and fasting glucose and 2‐h glucose levels in a series of sex‐stratified models adjusted for age, waist circumference, visceral and hepatic adiposity, and insulin resistance. Results In age‐adjusted models, lower levels of sex hormone‐binding globulin (β = −0.18, 95% CI −0.30, −0.06) and higher levels of free testosterone (β = 0.14, 95% CI 0.02, 0.26) were associated with elevated fasting glucose levels in South‐Asian women, whereas lower levels of sex hormone‐binding globulin (β = −0.14, 95% CI −0.26, −0.02) and lower levels of total testosterone (β = −0.12, 95% CI −0.24, 0.00) were associated with elevated fasting glucose levels in South‐Asian men. Adjustment for waist circumference, visceral adiposity and insulin resistance attenuated most of these associations, while adjustment for hepatic adiposity strengthened some of the observed associations. Similar results were found for 2‐h glucose levels. Conclusions Results were consistent with previous research, which suggests that endogenous sex steroid hormones are a risk factor for diabetes across multiple race/ethnic groups. Additional studies are needed to determine whether visceral fat is a mediator or confounder of associations between sex steroid hormone and glucose levels.